THE EFFECT OF CELEBRITY ENDORSMENT ON BRAND IMAGE AND TRUST BRAND AND IT'S IMPACT TO PURCHASEINTENTION CASE STUDY: OPPO SMARTPHONE - Rowlan Takaya (Universitas Trisakti, 2017)
The problem of this research investigates the importance of celebrity endorsment onThe brand image and brand trust towards of purchase intention on Oppo smartphone.The objectives of this research was analyzed the effect of celebrity endorsement to brand image, the effect of celebrity endorsement to brand trust, the effect brand image to purchase intention, the effect brand trust to purchase intention and the effect celebrity endorsement to purchase intention.The methodology of this research was survey research, where the instrument of this research is questioner. The population of this research is the citizen of Jakarta who knows the smartphone Oppo products. A sample of this research is 150 respondents using purposive sampling methode. Validity test of the instrument use Confirmatory Factor Analysis and the reliabilitas test use Alpha Cronbach technique. The methode analised with AMOS program version 22.0Finding and contribution in this research was celebrity endorsment positively affects the brand image and brand trust, brand image and brand trust positivily affects to purchase intention. Credibility is considered the most important characteristic of a brand and is a key focus of this research.Research limitations/ implication in this research was this research used a smartphone product to test the model and I collected data only from Jakarta. Such. A direct recommendation is that future studies should be conducted using a broarder consumer sampel to achieve generalizability and in another country may yield different result.